293 Malignant transformations in mature cystic teratoma of the ovary. 'rare, rarer, rarest'. (13th November 2020) - Billod, J; Wong, R
Abstract : Background: Malignant transformation (MT) in mature cystic teratoma of the ovary (MCTO) is a rare event with most common transformation is to squamous cell carcinoma. This paper presents the clinicopathologic characteristics of MT in MCTO. Methods: Pathological and clinical records were reviewed. Results: Between January 2016 and December 2019, of the 317 MCTO, there were 19 cases of malignant transformation with an incidence of 6%. Mean age of diagnosis was 52 years old (range 33–70 years old), of which 60% were aged 50 years old and above. Mean Gravidity and Parity is 3. Eleven out of 19 are squamous cell carcinoma (incidence:3.5%). The uncommon MT were adenocarcinoma (3) and mucinous carcinoma (3) at 1% incidence rates. A very rare MT reported in MCTO were carcinoid tumor (1) and follicular carcinoma (1). All cases had unremarkable preoperative CA125 value. The largest average diameter of MCTO with malignant transformation was 13 cm, of which 60% with right laterality. Five patients underwent fertility-sparing surgery. Ten patients were at Stage I, while 3, 4 and 2 patients were at Stage II, III, and IV respectively. Conclusion: MT in MCTO is not a common occurrence but should be considered in older patients with large tumor size despite a low preoperative tumor marker. Early diagnosis, appropriate surgery and adjuvant treatment improve survival.